A new method for the rapid detection of Atlantic cod (Gadus morhua), Pacific cod (Gadus macrocephalus), Alaska pollock (Gadus chalcogrammus) and ling (Molva molva) using a lateral flow dipstick assay - Taboada, Ledicia; Sánchez, Ana Cristina; Pérez Martín, Ricardo Isaac; González Sotelo, Carmen (Food Chemistry, 2017)
8 pages, 3 figures, 3 tables Species-specific lateral flow dipstick (LFD) assays for the identification of Atlantic cod (Gadus morhua), Pacific cod (Gadus macrocephalus), Alaska pollock (Gadus chalcogrammus) and ling (Molva molva) in food products were developed. The method comprises a PCR system with four sets of specific primers, for each target species. This step was also devised to dual-labeling of PCR products with biotin and 6-FAM, which are then easily read on a lateral flow dipstick, upon which these products are immobilized by a fixed biotin-ligand and visualized with anti-FAM antibody-coated gold nanoparticles. Sensitivity and selectivity were determined for each of the developed assays. Validation of the assays was performed with DNA extracted from commercial fish products, the identification of all samples by PCR-LFD was coherent with the results found with DNA sequencing. Target species were successfully detected in analyzed commercial samples, demonstrating the applicability of this method to the rapid analysis of food products The work was supported by the projects “GENTRASEA: Genetic traceability of fish products. Rapid methods with DNA hybridization probes” funded by Spanish Ministry of Science and Innovation and “LABELFISH: Atlantic network on genetic control of fish and seafood labelling and traceability.” Funded by Atlantic Area Programe (UE). The Spanish Ministry of Science and Innovation is gratefully acknowledged for the doctoral fellowship to Ledicia Taboada, who is a PhD student at the University of Santiago de Compostela Peer reviewed